DATASET FOR: Disentangling the origin of degradation in perovskite solar cells via optical imaging and Bayesian inference. - Dasgupta, A; Oliver, R D J; Lin, Y-H; Kober-Czerny, M; Ramadan, A J; Snaith, H J (University of Oxford, 2024)
Here we deposit the data and code necessary to generate the analysis found in our work. We have included: Simulation output from drift diffusion simulations; Photoluminescence imaging data (in a semi-raw and processed format); Outputs from our Bayesian analysis combining the two; and a clone of the code (from our public git repo) used to generate the analysis.